2017
DOI: 10.1080/02670836.2016.1215064
|View full text |Cite
|
Sign up to set email alerts
|

Review of principles and methods of severe plastic deformation for producing ultrafine-grained tubes

Abstract: Severe plastic deformation (SPD) is known to be the best method for producing bulk ultrafine-grained and nanostructured materials with excellent properties. Different SPD methods were developed that are suitable for sheet and bulk solid materials. During the past decade, efforts have been made to create effective SPD processes suitable for producing cylindrical tubes. In this paper, we review SPD processes intended to produce ultrafine-grained and nanostructured tubes, and their effects on material properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 142 publications
1
42
0
Order By: Relevance
“…In the last decade, fabrication of bulk multi-layered composites by severe plastic deformation (SPD) processes was considered and developed quickly because of some advantages of SPD over other processes such as casting, deposition and powder metallurgy [7]. So far, different successful SPD methods [8] were developed such as equal channel angular pressing (ECAP) [9] and rolling (ECAR) [10], tubular channel angular pressing [11,12], high-pressure torsion (HPT) [13,14] and accumulative roll bonding (ARB) [15]. The common features all of SPD methods are no change in the sample cross section after and before the process, capability to produce ultrafine grained (UFG) structures with high angle grain boundary and useable for different metals and alloys [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, fabrication of bulk multi-layered composites by severe plastic deformation (SPD) processes was considered and developed quickly because of some advantages of SPD over other processes such as casting, deposition and powder metallurgy [7]. So far, different successful SPD methods [8] were developed such as equal channel angular pressing (ECAP) [9] and rolling (ECAR) [10], tubular channel angular pressing [11,12], high-pressure torsion (HPT) [13,14] and accumulative roll bonding (ARB) [15]. The common features all of SPD methods are no change in the sample cross section after and before the process, capability to produce ultrafine grained (UFG) structures with high angle grain boundary and useable for different metals and alloys [16].…”
Section: Introductionmentioning
confidence: 99%
“…As is realized, the large amount of deformation load in pressing based processes is consumed to overcome the friction forces. 63,64) Orlov et al demonstrated the feasibility of upscaling of SPD technique by an integrated die combining conventional extrusion and ECAP as an integrated processing step. 65) As shown schematically in Fig.…”
Section: Integrated Extrusion and Equal Channel Angularmentioning
confidence: 99%
“…Around 120 variants of SPD methods have been introduced up to now, providing metallic materials of different shapes, such as rods, bars, billets, tubes, or sheets [99]. Even though various SPD techniques were successfully applied to conventional tube dimensions [103], and these techniques can provide advantages for micro-components, only a few published results exist concerning research on micro-tube SPD processes.…”
Section: Severe Plastic Deformation With a Focus On Micro-tube Fabricmentioning
confidence: 99%